Programme aid and development : beyond conditionality - White, Howard; Dijkstra, A. Geske (London ; New York : Routledge, 2003)
Using real world examples from countries such as Nicaragua, Tanzania and Vietnam this important contribution to the literature on development economics analyses the effectiveness of programme aid.
Includes bibliographical references and index.
oif 26/07/16
Loans
Keywords: Economic assistance; Economic assistance; Developing countries